Pelatihan Dan Pendampingan Bakteri Berbahaya Dalam Penyedap Makanan (Msg) Kepada Santri Pondok Pesantren Qur’any Jombang - Kurroti A'yun; Binti Masrufa (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
The purpose of this service is to describe the Training and Assistance of Dangerous Bacteria in Food Flavoring (MSQ) for Santri Pondok Pesantren Qur'any Jombang. Prior to the implementation of training and mentoring, first: literature study on the introduction of various types of bacteria, preparation of tools and materials for the practice of bacterial activity in food, determining the time of implementation and the duration of community service activities together with the implementing team, determining and preparing the material to be delivered in community service activities. The service activities are carried out in 2 groups, namely one group of male students and one group of female students. This is adapted to the conditions of assistance, namely Islamic boarding schools where all activities are separated between male students and female students. The result of the dedication is that the knowledge and understanding of the community to better maintain health has increased. The community's skills in processing food ingredients and finding natural flavoring ingredients are increasing. Given the enormous benefits of community service activities, it is necessary to hold similar training in other sub-districts as well as a wider target audience in collaboration with related agencies. There is continuity and monitoring of the program after this community service activity so that people can really get used to a healthy lifestyle, starting with things that are easy but contain many benefits.